IMPLEMENTASI PELAYANAN KESEHATAN MENURUT UNDANG-UNDANG NO. 24 TAHUN 2011 TENTANG BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) (Studi di RSUD Kertosono Kabupaten Nganjuk) - Binar Idha Meutia (Legal Spirit, 2020)
The purpose of this study was to analyze BPJS Health services in Kertosono District Hospital Nganjuk District, and to analyze the supporting and inhibiting factors of BPJS Health services in Kertosono District Hospital Nganjuk Regency. The results of this study are: First, health services in Kertosono Regional Hospital Nganjuk said to be very good, it is because of the commitment of the Kertosono Regional Hospital who want to provide health services according to good standards and based on public service standards to the community. Second, the supporting factors in providing services to patients are, the attitude of employees who are friendly and polite, the services provided are satisfactory and the flow is easy, there are poster announcements related to BPJS, clear goals and objectives, and sufficient financial. The inhibiting factors of HR owned by hospitals are not comparable to those treated (patients), frequent miscommunication between officers and patients, incomplete medical devices, inefficiency of the BPJS claim process, and arrears of payment from the BPJS.Keywords: Services, Health, Badan Penyelenggara Jaminan Sosial (BPJS)